(untitled) (Journal of Hama University, 2024)
The experiment was carried out in the greenhouse of the Faculty of Agricultural Engineering - Tishreen University - Latakia during the 2022-2023 agricultural season by planting seeds of four genotypes of Lathyrus sativus L. (Lattakani, Tartousi, Homsi, and Shami) in plastic bags with a capacity of 5 kg of soil consisting of (2 soil: 1 organic matter: 1 sand) were distributed according to a completely randomized design at a rate of three replicates for each treatment. The research aimed to study the most important morphological, physiological, production and quality characteristics of some genotypes of Jalapeno, using some statistical indicators for the studied characters in order to select the best of these types to be relied upon in subsequent breeding programmes. The studied genotypes differed among themselves in various morphological, physiological, productive and qualitative characteristics according to the genetic composition of each and the extent of its response to the environmental conditions accompanying growth, with the genotype Homsi being superior in many morphological characteristics, as the number of branches reached (13.66) branches/plant and the productivity reached the length of a pod (7) cm. With the possibility of cultivating the Jalapeno, Latakani and Tartousan varieties in dry and semi-arid areas due to their high proline content. Also, a difference was observed in the productive traits studied, which contributes to the widespread use of these models and their consideration as primary material in subsequent breeding program research.